2006
DOI: 10.1038/sj.onc.1209859
|View full text |Cite
|
Sign up to set email alerts
|

A positive feedback loop between hepatocyte growth factor receptor and β-catenin sustains colorectal cancer cell invasive growth

Abstract: Overexpressed or activated hepatocyte growth factor receptor, encoded by the MET proto-oncogene, was found in the majority of colorectal carcinomas (CRCs), whose stepwise progression to malignancy requires transcriptional activation of b-catenin. We here demonstrate that a functional crosstalk between Met and b-catenin signaling sustains and increases CRC cell invasive properties. Hepatocyte growth factor (HGF) stimulation prompts b-catenin tyrosine phosphorylation and dissociation from Met, and upregulates b-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 46 publications
3
80
0
Order By: Relevance
“…Nevertheless, it is yet not clear how hypothermia retarded β-catenin's degradation. As we have discussed, in the penumbra of normothermic brain, transient increases in β-catenin phosphorylation at 5h appear to correlate with β-catenin degradation at later time points, which is consistent with the notion that β-catenin phosphorylation results its degradation [9,11]. However, in the penumbra of hypothermic brains, phosphorylated β-catenin accumulated from 5 to 48 h after stroke while total β-catenin was not degraded, which contradicts the aforementioned hypothesis.…”
Section: Discussionsupporting
confidence: 35%
See 2 more Smart Citations
“…Nevertheless, it is yet not clear how hypothermia retarded β-catenin's degradation. As we have discussed, in the penumbra of normothermic brain, transient increases in β-catenin phosphorylation at 5h appear to correlate with β-catenin degradation at later time points, which is consistent with the notion that β-catenin phosphorylation results its degradation [9,11]. However, in the penumbra of hypothermic brains, phosphorylated β-catenin accumulated from 5 to 48 h after stroke while total β-catenin was not degraded, which contradicts the aforementioned hypothesis.…”
Section: Discussionsupporting
confidence: 35%
“…We found in this study that β-catenin phosphorylation transiently increased at 5h in the normothermic brain, and this hyper-phosphorylation was accompanied by a later degradation of total β-catenin. This correlation suggests that β-catenin phosphorylation progresses to degradation [9,11]. Furthermore, β-catenin might be phosphorylated by GSK3 β activity, as levels of phosphorylated GSK3 β transiently decreased from 5h to 24h, indicating increasedactivity during this period after stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that β-catenin accumulation, a hallmark of Wnt activation, is particularly enhanced in the invasion front and metastasized colon cancer cells, suggesting that promotion of Wnt/β-catenin signaling is important for malignant progression 8 . Growth factors PDGF and HGF, as well as inflammatory cytokine TNF-α, have been shown to promote Wnt/β-catenin signaling activity in tumor cells [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…In the network of signaling transduction, the positive feedback loop regulation plays important roles in determining the progressive nature of malignant cancer cells including cell proliferation [2][3][4][5] . Extracellular signal-regulated kinase 1/2 (ERK1/2), a major cellular proliferation signaling pathway, is involved in many positive feedback loops.…”
Section: Introductionmentioning
confidence: 99%